Bed isolation in experimental flap studies in rats: a dispensable procedure - Heimer, Sina Franziska; Müller, Wolf C.; Lass, Ulrike; Gebhard, Martha-Maria; Germann, Günter; Leimer, Uwe; Köllensperger, Eva; Reichenberger, Matthias (Annals of plastic surgery, 2013)
Review of the literature regarding rodent experimental flap models reveals fundamental differences in applied surgical procedures. Although some authors isolate the flap from its wound bed, others do not. This study was planned to investigate to what extent the insertion of a silicone sheet affects physiological wound healing in experimental flap surgery. An extended epigastric adipocutaneous flap (6 × 10 cm) was raised in 16 male Lewis rats. In the control group (group C), flaps were immediately inset without any intervention. In the experimental group (group M), a silicone sheet barrier was placed between the flap and the wound bed. Mean flap survival area and flap perfusion were evaluated. Microvessel density was visualized by immunohistochemistry, and semiquantitative real-time polymerase chain reaction addressed differential gene expression. All animals were investigated on postoperative day 5. Flap survival area and flap perfusion were found to be similar. Immunohistochemistry, however, demonstrated a significantly increased number of CD31-positive small vessels in group C. The insertion of the silicone sheet barrier (group M) was accompanied by a significantly enhanced expression of proinflammatory genes and a suppression of proangiogenic genes. Our results show that although the silicone membrane has no influence on the surgical outcome in terms of flap survival and perfusion, it does lead to significant molecular alterations in pathways involved in physiological wound healing. These alterations are artificially induced by the foreign body material and conceal the true driving forces of the healing process. As the latter might include relevant therapeutic targets to ameliorate surgical results, we regard wound bed isolation as a dispensable procedure in the study of rodent flap models.
Gesehen am 08.10.2021